1981
DOI: 10.1007/bf00008282
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dissolved heavy metals on attached diatoms in the Uintah Basin of Utah, U.S.A.

Abstract: The relationships of diatom species to dissolved heavy metals in the streams of the Uintah Basin of Utah were studied through four seasons of 1977-1978 . Niche center gradient analysis, cluster analysis and correlation analysis were performed . Achnanthes minutissima, Cyclotella meneghiniana, Cymbella minuta, Gomphonema parvulum, Navicula secreta var . apiculata, Nitzschia frustulum, Nitzschia frustulum var . perminuta, Nitzschia frustulum var . perpusilla, Nitzschia palea, and Synedra ulna appear to be indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Similar results reported by Kutka and Richards (1997) showed C. meneghiniana responded negatively and G. parvulum responded positively to ammonia diffusing pots in the field studies in a Minnesota river basin. Rushforth et al (1981) also confirmed G. parvulum exhibited a better performance with a high level of ammonia, while C. meneghiniana was stimulated by a high level of nitrate.…”
Section: Sensitivity Difference Of Typical Freshwater Diatoms On Ammosupporting
confidence: 81%
“…Similar results reported by Kutka and Richards (1997) showed C. meneghiniana responded negatively and G. parvulum responded positively to ammonia diffusing pots in the field studies in a Minnesota river basin. Rushforth et al (1981) also confirmed G. parvulum exhibited a better performance with a high level of ammonia, while C. meneghiniana was stimulated by a high level of nitrate.…”
Section: Sensitivity Difference Of Typical Freshwater Diatoms On Ammosupporting
confidence: 81%
“…Equally useful is the use of categories of alkalinity values in relation to diatom indicators (Descy, Empain & Lambinon, 1982). Rushforth et al, (1987) developed a similar 'niche center index' to place taxa on a weighted environmental gradient.…”
Section: Species Datamentioning
confidence: 99%
“…In addition, population response to heavy metals is significantly influenced by variations in natural environmental parameters, such as light and temperature (Rushforth et at., 1981). Hence biological monitoring programs based on community criteria are subject to considerable intrinsic error.…”
Section: Biological Impactmentioning
confidence: 99%